1995
DOI: 10.1093/jnci/87.16.1237
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Permeability Factor (Vascular Endothelial Growth Factor) Expression and Angiogenesis in Cervical Neoplasia

Abstract: These observations suggest that VPF is an important angiogenic factor in cervical neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
135
1
12

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(156 citation statements)
references
References 0 publications
8
135
1
12
Order By: Relevance
“…Third, HPV-16-encoded E6 and E7 viral oncoproteins have been implicated in the etiology of cervical cancer (Walboomers et al, 1999), as summarized in the introduction. Fourth, VEGF overexpression appears to be an important component of the angiogenic process in invasive squamous cell carcinoma of the cervix (Guidi et al, 1995;Sillman et al, 1981), similar to most other types of tumors. Increased VEGF expression and tumor vascularity have been observed in premalignant carcinoma of the cervix as well as high grade intraepithelial lesions and invasive carcinomas per se Weidner, 1994, 1997;Guidi et al, 1995;Tokumo et al, 1998) Given this information, we reasoned that HPV associated oncoproteins, particularly E6, may be responsible, at least in part, for VEGF production in various stage lesions of carcinoma of the cervix.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Third, HPV-16-encoded E6 and E7 viral oncoproteins have been implicated in the etiology of cervical cancer (Walboomers et al, 1999), as summarized in the introduction. Fourth, VEGF overexpression appears to be an important component of the angiogenic process in invasive squamous cell carcinoma of the cervix (Guidi et al, 1995;Sillman et al, 1981), similar to most other types of tumors. Increased VEGF expression and tumor vascularity have been observed in premalignant carcinoma of the cervix as well as high grade intraepithelial lesions and invasive carcinomas per se Weidner, 1994, 1997;Guidi et al, 1995;Tokumo et al, 1998) Given this information, we reasoned that HPV associated oncoproteins, particularly E6, may be responsible, at least in part, for VEGF production in various stage lesions of carcinoma of the cervix.…”
Section: Discussionmentioning
confidence: 83%
“…A similar relationship may also hold true for regulators of angiogenesis such as VEGF. With respect to HPVassociated cancers, high grade cervical dysplasia and invasive squamous cell carcinoma of the cervix are, like many other types of cancer, associated with angiogenesis (Smith-McCune and Weidner, 1994;Guidi et al, 1995;Sillman et al, 1981;Smith-McCune et al, 1997;Hove et al, 1999;Tokumo et al, 1998). However the mechanisms responsible for induction and maintenance of the angiogenic phenotype in cervical neoplasia are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins include cell adhesion molecules, proteindegrading enzymes and positive and negative angiogenesis factors (Brown and Giaccia, 1994;Dachs and Stratford, 1996). As an example, the expression of vascular endothelial growth factor, a positive angiogenesis factor known to be involved in the angiogenesis of cervical carcinoma (Guidi et al, 1995) is up-regulated significantly under hypoxic conditions both in vitro and in vivo (Plate et al, 1992;Shweiki et al, 1992;Waleh et al, 1995;Mazure et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a dimeric glycoprotein with four spliced variants consisting of 121, 165, 189 and 206 amino acid residues expressing almost identical biological activities by binding to specific class III receptor tyrosine kinases (flt-l and KDR) (Neufeld et al, 1996;Terman and Dougher-Vermazen, 1996). Recently, Guidi et al (1995) and our group (BancherTodesca et al, 1997;Obermair et al, 1997) reported that the presence of VEGF is associated with neoplastic transformation in cervical (CIN) and in vulvar intraepithelial neoplasia (VIN), suggesting that increasing VEGF may represent an early event in the carcinogenic process.…”
mentioning
confidence: 99%